2015
DOI: 10.1093/aobpla/plv024
|View full text |Cite
|
Sign up to set email alerts
|

Winter warming delays dormancy release, advances budburst, alters carbohydrate metabolism and reduces yield in a temperate shrub

Abstract: Global climate models predict an increase in the mean surface air temperature, with a disproportionate increase during winter. This study documents that even a very modest temperature increase during the colder periods of a plant's annual cycle may delay dormancy release and advance bud burst and flowering in blackcurrant, but the magnitude of the responses varies between genotypes differing in chilling requirement. Winter warming additionally has a large carryover effect into the growing season by reducing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 61 publications
5
18
1
Order By: Relevance
“…This is in agreement with observations in blackcurrant ( Ribes nigrum ) that winter warming decreases the sucrose in stem (Pagter et al. ). Sugar has been considered to be one of the most important factors acting as osmolytes or antioxidants in plant cold tolerance (Sasaki et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with observations in blackcurrant ( Ribes nigrum ) that winter warming decreases the sucrose in stem (Pagter et al. ). Sugar has been considered to be one of the most important factors acting as osmolytes or antioxidants in plant cold tolerance (Sasaki et al.…”
Section: Discussionsupporting
confidence: 93%
“…3). This is in agreement with observations in blackcurrant (Ribes nigrum) that winter warming decreases the sucrose in stem (Pagter et al 2015). Sugar has been considered to be one of the most important factors acting as osmolytes or antioxidants in plant cold tolerance (Sasaki et al 1996, Keunen et al 2013 might have contributed to their higher susceptibility to low temperature stress, as compared with plant grown under normal soil temperature.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies show that spring events, such as leaf unfolding or needle flush, are particularly sensitive to temperature (Lechowicz, 1995;Sarvas, 1972Sarvas, , 1974. In accordance with our results on the after effect of the treatments in 2015, Fu et al (2012) found that Betula (Pagter, Andersen, & Andersen, 2015), and bud break is associated with low levels of soluble sugars (Lipavská, Svobodová, & Albrechtová, 2001). In this case, the enhanced temperature would have reduced the sugar concentrations, as was also seen in B. pendula seedlings (Riikonen et al, 2013), which could be the mechanism behind the temperature-forced bud break in 2014 and 2015.…”
Section: Discussionsupporting
confidence: 88%
“…It can be speculated that in addition to the carry‐over effect of the temperature treatment, the enhanced bud break in intact individuals in 2015 could have also resulted from the previous year high autumn temperature which might have influenced the subsequent bud burst. Elevated temperature can alter the sugar levels in buds (Pagter, Andersen, & Andersen, ), and bud break is associated with low levels of soluble sugars (Lipavská, Svobodová, & Albrechtová, ). In this case, the enhanced temperature would have reduced the sugar concentrations, as was also seen in B. pendula seedlings (Riikonen et al., ), which could be the mechanism behind the temperature‐forced bud break in 2014 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The CD accumulation then departs from that plateau in the autumn just before GDD accumulation ceases. Between these dates, T avg ≥ T base and vegetation defenses against freezing are limited while net primary productivity is generally dedicated to growth and reproduction [Schenker et al, 2014;Vitasse et al, 2014;Körner, 2015;Pagter et al, 2015]. Our resulting plateau-based growing season is several days longer than the frost-free season for the same year.…”
Section: 1002/2016jd025190mentioning
confidence: 93%